Electron beam dynamics and channeling radiation simulation in crystal - Bashmakov, Yu.A.; Polozov, S.M. (Вопросы атомной науки и техники, 2014)
2D code was designed for the simulation and simulation algorithms and methods are discussed in this report. The planar channeling is studying. Results of electron dynamics and radiation simulations are presented. The designed algorithm can be also used to separate channeled and dechanneled particles. The dependence of the oscillation period versus electron oscillation amplitudes is simulated. It allows defining of the radiation spectrum. The fundamental and high order harmonics radiation probability is discussed. The probability of radiation spectrums is presented.